Translation of Personal Names in Klingon “Hamlet” - Chiara Meluzzi (RiCognizioni)
The translation of literary classics into constructed languages (ConLangs), particularly artificial languages (ArtLangs) like Klingon, offers unique insights into the interplay between language, culture, and translation theory. This paper focuses on the Klingon adaptation of Shakespeare’s Hamlet, with a particular emphasis on the treatment of proper names. Through detailed analysis, the study explores how linguistic and cultural constraints of Klingon phonology influenced the adaptation of English names while maintaining their recognisability for readers.